Стан системи гіпофіз – надниркові залози на тлі замісної терапії рекомбінантним гормоном росту у дітей, хворих на соматотропну недостатність - Вишневська, О. А.; Большова, О. В. (Clinical Endocrinology and Endocrine Surgery, 2012)
The purpose of this study was to investigate cortisol blood levels in in children with somatotropic insufficiency during rhGH – therapy. Study parameters were assessed at baseline and after 6 and 12 months of rhGH replacement. Children with somatotropic insufficiency show statistically significant decrease of blood cortisol levels during long – term rhGH – replacement. These data indicate that rhGH-replacement is associated with hypocorticism, occured during rhGH- therapy. GH-deficient patients need additional hormone replacement therapy with glucocorticoids and careful monitoring of blood cortisol level every 3 months during rhGH-replacement.